Legislative measures for the agri-food sector in times of COVID-19 in Spain - Muñiz Espada, Esther; López Torres, Juan Manuel (Przegląd Prawa Rolnego, 2020)
The epidemiological situation that the health crisis has generated as a consequence of COVID-19 in Spain has entailed the adoption of certain measures in almost all areas of the economy. It has even been used to modify aspects that were not justified by the urgency or alarm of the health situation. The essential nature recognised for the agri-food activity (agriculture, livestock, aquaculture, fishing and food industry) has made it possible to maintain the activity throughout the entire state of alarm. This exceptional situation has demanded extraordinary urgent measures counteracting the economic and social impact of COVID-19. In the agricultural sector itself, Royal Decree-Law 13/2020 of 7 April 2020 sought to establish as a measure the compatibility of unemployment benefits or other social or labor benefits with the performance of agricultural tasks, attracting people in a situation of unemployment or cessation of activity, as well as those workers whose contracts have been temporarily suspended or those migrants whose work permit was to end in the period between the declaration of the State of alarm and 30 June 2020 to attend to the needs of the existing manpower. Likewise, measures have been adopted to facilitate the inclusion of workers in the Special System of Self-Employed Agrarian Workers (SETA), with a lower cost for the subjects received, through Royal Decree-Law 15/2020, of 21 April 2020, of complementary urgent measures to support the economy and employment. For this, all the conditions that have been until now related to income are eliminated. Lastly, the Royal Decree-Law 19/2020 of 26 May 2020, which adopts complementary measures in agrarian, agricultural, scientific, economic, employment, Social Security and tax matters to mitigate the effects of COVID-19, has now been extended for three months the content of the Royal Decree-Law 13/2020, with the aim of ensuring sufficient manpower to meet the summer farming needs.